Oxidation of hepatic carnitine palmitoyl transferase-I (CPT-I) impairs fatty acid beta-oxidation in rats fed a methionine-choline deficient diet. - Gaetano Serviddio (Public Library of Science (PLoS), 2011)
There is growing evidence that mitochondrial dysfunction, and more specifically fatty acid β-oxidation impairment, is involved in the pathophysiology of non-alcoholic steatohepatitis (NASH). The goal of the present study was to achieve more understanding on the modification/s of carnitinepalmitoyltransferase-I (CPT-I), the rate-limiting enzyme of the mitochondrial fatty acid β-oxidation, during steatohepatitis. A high fat/methionine-choline deficient (MCD) diet, administered for 4 weeks, was used to induce NASH in rats.We demonstrated that CPT-I activity decreased, to the same extent, both in isolated liver mitochondria and in digitonin-permeabilized hepatocytes from MCD-diet fed rats.At the same time, the rate of total fatty acid oxidation to CO(2) and ketone bodies, measured in isolated hepatocytes, was significantly lowered in treated animals when compared to controls. Finally, an increase in CPT-I mRNA abundance and protein content, together with a high level of CPT-I protein oxidation was observed in treated rats. A posttranslational modification of rat CPT-I during steatohepatitis has been here discussed.